2017
DOI: 10.15666/aeer/1501_457472
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sport Tourism on Temperate Grassland Communities (Duna-Ipoly National Park, Hungary)

Abstract: Abstract. Effects of sport tourism were examined in dry grassland stands with fix sample plots in four sites of strictly protected areas of Buda Mountains and Pilis in Duna-Ipoly National Park in the vicinity of Budapest (Hungary). The size of all sample plots was 2×2 m in all sites, we designated 4×10 sampling quadrats and 4×10 control quadrats. The date of surveying was in May and July in 2013. The sampling sites were exposed to different type of illegal sport activities. The questions we tried to answer wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Also, in spite of recorded differences in the degree of cover-abundance of species representing particular life forms, depending on trail width and plot location, the similar patterns of life form spectra noticed in the majority of the study areas indicate the rejection of hypothesis (v) about the variability of species life form spectra. The performed investigations evidencing a dominance of hemicryptophytes and chamaephytes supports the findings of Dobay et al [74], arguing that the species representing the aforementioned life forms are often found in grassland areas. Roovers et al [38] observed the dominance of hemicryptophytes regardless of level recreational use in meadows, heaths, and forests, whilePescott and Stewart [75] added that vegetation dominated by hemicryptophytes recovers from trampling to a greater extent than vegetation dominated by other life forms.…”
Section: The Species Groups Characteristicssupporting
confidence: 88%
“…Also, in spite of recorded differences in the degree of cover-abundance of species representing particular life forms, depending on trail width and plot location, the similar patterns of life form spectra noticed in the majority of the study areas indicate the rejection of hypothesis (v) about the variability of species life form spectra. The performed investigations evidencing a dominance of hemicryptophytes and chamaephytes supports the findings of Dobay et al [74], arguing that the species representing the aforementioned life forms are often found in grassland areas. Roovers et al [38] observed the dominance of hemicryptophytes regardless of level recreational use in meadows, heaths, and forests, whilePescott and Stewart [75] added that vegetation dominated by hemicryptophytes recovers from trampling to a greater extent than vegetation dominated by other life forms.…”
Section: The Species Groups Characteristicssupporting
confidence: 88%
“…Having developed rapidly in recent years as a special field of interest in the travel industry (Alexandris and Kaplanidou, 2014;Alsafawi, 2017;Dobay et al, 2017), sports tourism has emerged around the needs of individuals. Sports tourism can be active or passive, and refers to the traveling organized with commercial or noncommercial motives to compete or participate in physical activities, watch physical activities or visit places related to such activities (Hinch and Higham, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hinch and Ito (2018) have stated that sports tourism is developing in Japan but that this development also highlights the matter of sustainability. Dobay et al (2017) have attempted to find out whether nature protection works are effective in four different drylands in Duna-Ipoly National Park in the Buda Mountains and Pilis region in Budapest by examining the effects of sports tourism. Hinch and Holt (2017) aimed to gain insight into the sustainability of active sports tourism activities by emphasizing the importance of focusing on strategies for improving said activities and using these strategies intensively in the promotion and marketing of activities.…”
Section: Related Studiesmentioning
confidence: 99%
“…Besides musical features, the organizers of both festivals put great emphasis on boosting the touristic, cultural and sport life of visitors. According to researchers, sports tourism is the most dynamically developing area of tourism (Dobay et al, 2016;Gibson, 2010). Sport and Tourism are not just about the management and operations of mega events; they also concern offering the consumer specific Sport and Tourism related services and experiences.…”
Section: Literature Review 21 the Role Of Festivals In The Life Of mentioning
confidence: 99%